2008
DOI: 10.1136/jech.2007.065367
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol outlet density, perceived availability and adolescent alcohol use: a multilevel structural equation model

Abstract: Perceived availability and drinking volume appear to be shaped by the adolescents' social and physical environments. Adolescents who have a variety of opportunities to obtain alcohol might develop the impression that underage drinking is common and socially endorsed. Consequently, preventive actions to curb adolescent alcohol consumption should take into account the social acceptance of drinking and the physical availability of alcohol in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 35 publications
3
69
0
4
Order By: Relevance
“…We found that general and on-premises outlet density was positively related to an increased risk of recent alcohol use and risky drinking among adolescents living in metropolitan and regional areas. Previous studies have found on-premises density to be associated with adolescent drinking [7,18]. However, few studies have examined the association between general licenses, such as hotels and taverns, and adolescent drinking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that general and on-premises outlet density was positively related to an increased risk of recent alcohol use and risky drinking among adolescents living in metropolitan and regional areas. Previous studies have found on-premises density to be associated with adolescent drinking [7,18]. However, few studies have examined the association between general licenses, such as hotels and taverns, and adolescent drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the relative influence of off-premises and on-premises outlet density also indicate conflicting findings. While some have reported positive relationships between higher on-premises -but not off-premises -outlet density and drinking frequency and quantity consumed [17,18], the opposite pattern has also been found [19,20]. Further, Truong and Sturm [7] reported a link between on-and off-premises outlet density in urban areas and binge drinking, but not with consuming alcohol in the previous 30 days.…”
Section: Introductionmentioning
confidence: 98%
“…In the literature on off-premise alcohol outlet density (but not specifically on sales times), a large study in Australia found that higher density of off-premise outlets was associated with significant increases in the chances of heavy drinking (Livingston, Laslett, & Dietze, 2008), while a similar study in California, US, found an increased outlet density lead to increased likelihood of heavy drinking but not of drinking per se (Truong & Sturm, 2009). Studies of adolescents in New Zealand (Huckle, Huakau, Sweetsur, Huisman, & Casswell, 2008) and in California (Chen, Grube, & Gruenewald, 2010) report a positive association between consumption and total and off-premise density respectively, whereas for similar age groups in Switzerland Kuntsche et al (Kuntsche, Kuendig, & Gmel, 2008) find increased on-site drinking with increased density, but no link with off-premise outlets. However, a study in the Netherlands, using a representative population sample reports the opposite, with the association being strong for alcohol shops but not bars (van Oers & Garretsen, 1993), which is confirmed by an older (before privatisation of alcohol stores) Canadian study (Rootman & Oakey, 1973).…”
Section: Instrumental Variablementioning
confidence: 96%
“…Other studies found the density of alcohol outlets to be correlated with individual drinking (Kypri, Bell, Hay, & Baxter, 2008), quantities consumed among teenage drinkers (Huckle, Huakau, Sweetsur, Huisman, & Casswell, 2008), and perceived availability and volume of drinking among adolescents (Kuntsche, Kuendig, & Gmel, 2008). Furthermore, the density of packaged liquor outlets was found to be significantly associated with very high-risk drinking in ------IJADR 5(2) ------Australia (Livingston, Laslett, & Dietze, 2008).…”
mentioning
confidence: 92%